A Molybdenum(VI) Complex of 5-(2-pyridyl-1-oxide)tetrazole: synthesis, structure, and transformation into a MoO3-Based hybrid catalyst for the epoxidation of Bio-Olefins - Nunes, Martinique S. (2023)
The discovery of heterogeneous catalysts synthesized in easy, sustainable ways for the valorization of olefins derived from renewable biomass is attractive from environmental, sustainability, and economic viewpoints. Here, an organic–inorganic hybrid catalyst formulated as [MoO3 (Hpto)]·H2O (2), where Hpto = 5-(2-pyridyl-1-oxide)tetrazole, was prepared by a hydrolysis– condensation reaction of the complex [MoO2Cl2 (Hpto)]·THF (1). The characterization of 1 and 2 by FT-IR and Raman spectroscopies, as well as 13C solid-state NMR, suggests that the bidentate N,O-coordination of Hpto in 1 (forming a six-membered chelate ring, confirmed by X-ray crystallography) is maintained in 2, with the ligand coordinated to a molybdenum oxide substructure. Catalytic studies suggested that 2 is a rare case of a molybdenum oxide/organic hybrid that acts as a stable solid catalyst for olefin epoxidation with tert-butyl hydroperoxide. The catalyst was effective for converting biobased olefins, namely fatty acid methyl esters (methyl oleate, methyl linoleate, methyl linolenate, and methyl ricinoleate) and the terpene limonene, leading predominantly to the corresponding epoxide products with yields in the range of 85–100% after 24 h at 70 ◦C. The versatility of catalyst 2 was shown by its effectiveness for the oxidation of sulfides into sulfoxides and sulfones, at 35 ◦C (quantitative yield of sulfoxide plus sulfone, at 24 h; sulfone yields in the range of 77–86%). To the best of our knowledge, 2 is the first molybdenum catalyst reported for methyl linolenate epoxidation, and the first of the family [MoO3 (L)x] studied for methyl ricinoleate epoxidation.